Current Research Trends on Last-Mile Logistics in Latin America during the Period 2017-2021 - Mayer Aguirre, Edgar Andre; Matta Jara, Angela Nalda; Cuzcano Ramos, Luiggi Jair; Alfaro Portilla, Pedro Antonio; Guzmán Guimaraes, Alexandra Angelica; Moscoso Cuaresma, Julio Ricardo; Jauregui Arroyo, Ralphi Ricardo (LACCEI, 2024)
The objective of this research is to determine the impact of current research trends on last-mile logistics in Latin America during the period 2017-2021. To achieve this, three specific objectives were established to delve deeply into the investigation. Regarding the research methodology, a systematic review of scientific literature from the Scopus database was conducted, emphasizing current trends such as e-commerce, environmental awareness, and cost reduction. As for the paper information, trends in last-mile logistics currently observed were taken into account, with a large percentage of publications falling into Q1 (68.4%), Q2 (26.3%), and Q3 (5.3%). Likewise, these trends in last-mile logistics are examined in relation to Latin American countries; this will allow us to address the issue of the impact of current research trends on last-mile logistics.